PENGARUH RASIO KEUANGAN TERHADAP PROFITABILITAS PADA PT BANK SHINHAN INDONESIA TAHUN 2020-2024 - Maarebia, Elince Jane Kirsten; Listiawati, Rodiana (Politeknik Negeri Ambon, 2025)
Introduction: This study aims to analyze the impact of financial ratios on profitability at Bank Shinhan Indonesia from 2020 to 2024. Prof|itab|il|ity |is measured by Return on Assets (ROA), while the f|inanc|ial rat|ios tested |include Non-Perform|ing Loan (NPL), Loan to Depos|it Rat|io (LDR), Net |Interest Marg|in (N|IM), and the rat|io of Operat|ing Expenses to Operat|ing |Income (BOPO).Methods: The method used |in this study |is quantitative | with multiple | linear regression analysis | techniques. The data used is from fireports. Results: The results showed that part|ially, Non-Perform|ing Loan and Operat|ing Expenses to Operat|ing |Income had a negat|ive and s|ign|if|icant effect on Return on Assets, wh|ile Net |Interest Marg|in had a pos|it|ive and s|ign|if|icant effect, and Loan to Depos|it Rat|io had a pos|it|ive but |ins|ign|if|icant effect. S| Simultaneously, all four |independent variables have a significant impact on Return on Assets